(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
This work is concerned with the asymptotic behaviors of solutions to a class of non-autonomous stochastic Ginzburg-Landau equations driven by colored noise and deterministic non-autonomous terms defined on thin domains. The existence and uniqueness of tempered pullback random attractors are proved for the stochastic Ginzburg-Landau systems defined on (n + 1)-dimensional narrow domain. Furthermore, the upper semicontinuity of these attractors is established, when a family of (n + 1)-dimensional thin domains collapse onto an n-dimensional domain.